Stability and content of anthocyanins in Peruvian purple potato INIA 328 - Kulli Papa - Neciosup Puican, Antony Alexander (2024)
The influence of temperature, extraction time and solvent ratio on the anthocyanin content extracted from Peruvian purple potatoes INIA 328 – KULLI were investigated using conventional extraction with acidified ethanolic aqueous solvent. The preservation rate (R), thermal degradation rate (k) and the half-life (t1/2) of purple potatoes anthocyanin extract at different temperatures were determined. In addition, the color change of the anthocyanin extract was examined against different pH using UV–Visible spectroscopy. The results showed an anthocyanin content of 75.71 mg/100g of fresh weight (FW) obtained by an extraction temperature of 40 °C, for 4 h and using a solvent ratio of 5 mL/g. On the other hand, thermal kinetic degradation indicates that 98 % of the anthocyanin content can be preserved for up to 6 h at 40 °C. Better results were observed by keeping anthocyanin solutions at 4 °C in the absence of light, reaching a preservation rate of 99 % after one month of storage.